Pathways to sustainability: empowering indigenous communities through recycling education - Hammad Ahmad Khan, Hafizah; Ahmad, Nabila; Mohd Yusof, Noorlailahusna; Anuar, Azyyati; Ahmad Zawawi, Azlyn (Universiti Teknologi MARA, Kedah, 2024)
Recycling is a critical component of sustainable waste management, helping to conserve resources, reduce pollution, and mitigate climate change. Despite its importance, awareness and participation in recycling activities remain low particularly among indigenous populations who often have limited exposure to modern environmental practices. This study investigates the impact of a recycling awareness program conducted within an indigenous community in Cameron Highlands, Pahang, Malaysia. The program included a pre-program survey to assess participants' awareness, understanding, and participation in recycling activities, followed by an educational session on general recycling practices and e-waste management. A post-program survey was conducted to measure the effectiveness of the program. The use of paired sample ttests reveals significant improvements in participants' knowledge and attitudes toward recycling. The findings provide compelling evidence that targeted educational programs can significantly enhance recycling awareness and participation within indigenous communities, contributing to broader environmental sustainability goals. The study underscores the need for the implementation of similar programs in other less exposed communities as well as continuous engagement and collaboration with local authorities to sustain and expand recycling initiatives.